The seismic response of structural outrigger systems in the tall buildings - Husain Mohamed (Institut za istrazivanja i projektovanja u privredi, 2021)
One of the advanced structural systems that have been applied in tall buildings to improve the building strength during quake loads is the outrigger system. Most of the previous researches interested to study the behavior of steel outrigger truss system, although the hard connection between the concrete and steel members may give us the inaccurate output. For that, This research aims to find the best structural concrete outrigger system by performing a comparison between two structural outrigger systems, the wall beam outrigger system, and the vierendeel outrigger system which makes the building facing strong actual earthquakes. All the models were analyzed in the advanced Midas-Gen software program and the building response was studied under El-Centro time history earthquake load. And also, finding the best outrigger position through the building height when the outrigger is applied in one and two stories. This comparison is built on different parameters as storey drift, storey drift ratio, and the base storey overturning moment. The results showed that a one-storey wall beam structural system is better than two stories vierendeel structural system when these systems are applied as an outrigger system. The best position for one storey outrigger is about 0.45 of the total building height and for the two stories outrigger, the 0.20 and 0.45 of the total building height are the best positions. Overall, the concrete outrigger systems are an effective structural system to make the tall buildings facing the earthquake loads.